Does Location of Epicardial Adipose Tissue Correspond to Endocardial High Dominant Frequency or Complex Fractionated Atrial Electrogram Sites During Atrial Fibrillation? - Nagashima, Koichi; Okumura, Yasuo; Watanabe, Ichiro; Nakai, Toshiko; Ohkubo, Kimie; Kofune, Masayoshi; Mano, Hiroaki; Sonoda, Kazumasa; Hiro, Takafumi; Nikaido, Mizuki; Hirayama, Atsushi (Circulation. Arrhythmia and electrophysiology, 2012)
BACKGROUND—Although increased epicardial adipose tissue (EAT) volume is known to be associated with increased prevalence of atrial fibrillation (AF), the exact mechanisms are unclear. Therefore, we investigated whether EAT locations were associated with high dominant frequency (DF) sites or complicated fractionated atrial electrogram sites during AF. METHODS AND RESULTS—Three-dimensional reconstruction computed tomography images depicting EAT volumes (obtained by 320-detector-row multislice computed tomography) were merged with NavX-based DF and complicated fractionated atrial electrogram maps obtained during AF for 16 patients with paroxysmal AF and for 18 patients with persistent AF. Agreement between locations of the EAT, especially EAT surrounding the left atrium, and of high DF or complicated fractionated atrial electrogram sites was quantified. In addition, serum biomarker levels were determined. EAT surrounding the left atrium volumes was significantly greater in patients with persistent AF than in patients with paroxysmal AF (52.9 cm [95% CI, 44.2–61.5] versus 34.8 cm [95% CI, 26.6–43.0]; P=0.007). Serum high-sensitivity C-reactive protein and interleukin-6 levels were significantly higher in persistent AF patients than in paroxysmal AF patients (median high-sensitivity C-reactive protein, 969 ng/mL [interquartile range, 307–1678] versus 320 ng/mL [interquartile range, 120–660]; P=0.008; median interleukin-6, 2.4 pg/mL [interquartile range, 1.7–3.2] versus 1.3 [interquartile range, 0.8–2.4] pg/mL; P=0.017). EAT locations were in excellent agreement with high DF sites (κ=0.77 [95% CI, 0.71–0.82]) but in poor agreement with complicated fractionated atrial electrogram sites (κ=0.22 [95% CI, 0.13–0.31]). CONCLUSIONS—Increased EAT volume and elevation of inflammatory biomarkers are noted in persistent AF rather than paroxysmal AF patients. High DF sites are located adjacent to EAT sites. Thus, EAT may be involved in the maintenance of AF.